Genetic Toxicity Studies of the Ketogenic Ester Bis Hexanoyl (R)-1, 3-Butanediol. (May 2021) - Stubbs, Brianna J.; Nikiforov, Andrey I.; Rihner, Marisa O.; Weston, Sari; Higley, Nancy; Roy, Shambhu; Dakoulas, Emily; Verdin, Eric; Newman, John C.
A series of studies was conducted to assess the genetic toxicity of a novel ketone ester, bis hexanoyl (R)-1, 3-butanediol (herein referred to as BH-BD), according to Organization for Economic Co-operation and Development testing guidelines under the standards of Good Laboratory Practices. In bacterial reverse mutation tests, there was no evidence of mutagenic activity in any of the Salmonella typhimurium strains tested or in Escherichia coli strain WP2 uvr A, at dose levels up to 5, 000 μg/plate in the presence or absence of Aroclor 1254-induced rat liver (S9 mix) for metabolic activation. In the in vitro micronucleus test using human TK6 cells, BH-BD did not show a statistically significant increase in the number of cells containing micronuclei when compared with concurrent control cultures at all time points and at any of the concentrations analyzed (up to 100 μg/mL, final concentration in culture medium), with and without S9 mix activation. In the in vivo micronucleus test using Sprague Dawley rats, BH-BD did not show a statistically significant increase in the incidence of micronucleated polychromatic erythrocytes relative to the vehicle control group. Therefore, BH-BD was concluded to be negative in all 3 tests. These results support the safety assessment of BH-BD for potential use in food.